The Relationship Between Parenting Styles And Parental Eating Behavior Towards Picky Eating Behavior In Preschool Children - Ranti Wulan Safitri, Desti; Rima Berlian Putri; Ricky Riyanto Iksan; Maria Susila Sumartiningsih (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2025)
Background: Picky eater is a condition in which children exhibit selective eating behavior, such as refusing to try new foods or only wanting to eat certain types of food. This habit can have a negative impact on nutritional adequacy, growth, and children's ability to interact socially. According to WHO, around 28.7% of toddlers in the world experience growth problems, and Indonesia is ranked third in Southeast Asia in this regard. One of the factors that can influence the emergence of picky eating behavior is parenting and parental eating habits. Research Objective: This is to determine the relationship between parenting and parental eating behavior with the tendency of children to become picky eaters. The design uses quantitative descriptive correlation, involving 73 respondents. Data were analyzed using the chi-square test. Results: The study showed a significant relationship between parenting and parental eating behavior with picky eating behavior in preschool children (p = 0.001). Conclusion: that inappropriate parenting can increase the risk of children becoming picky eaters by 5.8 times, while poor eating behavior from parents can increase the risk by up to 8.3 times (OR = 5.8; 8.3). Therefore, it is important for parents to implement supportive parenting styles and demonstrate healthy eating habits as an example for their children.